Measure distance using laser at small construction / Muhammad Mulhim Md Jani & Mohd Adib Afham Azlin - Md Jani, Muhammad Mulhim; Afham Azlin, Mohd Adib (2015)
The project is actually an alternative of the existing measuring devices in the market. The main idea of this project is to invent a new measuring device that resemble with the advance measuring devices in terms of its operation, but with lower production cost. Based on the site analysis, people who work at small construction site usually use the conventional method such as measuring tape as it cost effective and user-friendly. However, the conventional device has its limitation in measuring longer distance and cannot be handled by single person. The advance measuring device such as reflector less total station only worth for big budget project like housing areas or construction in urban areas. Hence, a new measuring device is developed by using only the basic concept of simple Pythagoras Theorem in order to overcome all of these problems